SOCIAL CAPITAL AND FARMERS' DECISION TO CULTIVATE PULU MANDOTI EMAS (PME) LOCAL RICE: A PROBIT MODEL - Saputra, Muhammad Taufik; Mulyo, Jangkung Handoyo; Darwanto, Dwijono Hadi (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Salukanan Village, Enrekang Regency, is the production center of inherited local rice through generations, known as